Measuring safety in older adult care homes: a scoping review of the international literature. Issue 3 (11th March 2021) - Rand, Stacey; Smith, Nick; Jones, Karen; Dargan, Alan; Hogan, Helen
Abstract : Background: Safety is a key concern in older adult care homes. However, it is a less developed concept in older adult care homes than in healthcare settings. As part of study of the collection and application of safety data in the care home sector in England, a scoping review of the international literature was conducted. Objectives: The aim of the review was to identify measures that could be used as indicators of safety for quality monitoring and improvement in older adult residential or nursing care homes. Sources of evidence: Systematic searches for journal articles published in English language from 1 January 1970, without restriction to the study location or country, were conducted in Web of Science, Scopus and PubMed on 28 July 2019. Eligibility criteria: Inclusion criteria were: peer-reviewed journal articles; qualitative or quantitative studies of older adult nursing and/or residential care homes; and related to any aspect of safety in care homes, including the safety of healthcare provision in the care home. A total of 45 articles were included after review of the title/abstract or full text against the inclusion criteria. Charting methods: Key information was extracted and charted. These findings were then mapped to the Safety Measurement and Monitoring Framework in healthcare (SMMF), adapted by the research team to reflect the care home context, to determine the coverage of different aspects of safety, as well as potential gaps. Results and conclusions: Systematic searches for journal articles published in English language from 1 January 1970, without restriction to the study location or country, were conducted in Web of Science, Scopus and PubMed on 28 July 2019. Inclusion criteria were: peer-reviewed journal articles; qualitative or quantitative studies of older adult nursing and/or residential care homes; and related to any aspect of safety in care homes, including the safety of healthcare provision in the care home. A total of 45 articles were included after review of the title/abstract or full text against the inclusion criteria. Key information was extracted and charted. These findings were then mapped to the Safety Measurement and Monitoring Framework in healthcare (SMMF), adapted by the research team to reflect the care home context, to determine the coverage of different aspects of safety, as well as potential gaps. The findings indicate that there are a range of available safety measures used for quality monitoring and improvement in older adult care homes. These cover all five domains of safety in the SMMF. However, there are potential gaps. These include user experience, psychological harm related to the care home environment, abusive or neglectful care practice and the processes for integrated learning. Some of these gaps may relate to challenges and feasibility of measurement in the care home context.